2006
DOI: 10.1021/ma061380x
|View full text |Cite
|
Sign up to set email alerts
|

Living Character of Polymer Chains Prepared via Nitroxide-Mediated Controlled Free-Radical Polymerization of Methyl Methacrylate in the Presence of a Small Amount of Styrene at Low Temperature

Abstract: This article follows a previous study (Macromolecules 2005, 38, 5485) demonstrating that the nitroxide SG1-mediated polymerization of methyl methacrylate can be achieved at 90 °C with high conversion and high quality of control by introducing a small amount of styrene. In this work, the resulting polymer was characterized and the presence of SG1-based alkoxyamine at the polymer chain-end was identified, supporting the livingness of the macromolecules. In particular, it was shown that the alkoxyamine end group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
279
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 217 publications
(293 citation statements)
references
References 26 publications
13
279
1
Order By: Relevance
“…However, no ambiguous discussions were provided on the origin of this effect. At a first glance, although this led to apparently contradictory measurements [10,15,16], such small differences in k d may look unimportant, but nevertheless, we have recently shown that the fate of NMP [11,12,17] and the occurrence of side-reactions [18] depends on such small differences.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, no ambiguous discussions were provided on the origin of this effect. At a first glance, although this led to apparently contradictory measurements [10,15,16], such small differences in k d may look unimportant, but nevertheless, we have recently shown that the fate of NMP [11,12,17] and the occurrence of side-reactions [18] depends on such small differences.…”
Section: Introductionmentioning
confidence: 96%
“…During the last decade, the effect of the penultimate unit on the C-ON bond was poorly investigated, and seemingly contradictory results were published concerning polystyryl-TEMPO alkoxyamines. Until recently, it has been shown [10] that the penultimate unit may exert a dramatic effect on the C-ON bond homolysis and, consequently, on the fate of NMP [11,12]. Georges and colleagues [13] measured the C-ON bond homolysis in the diastereoisomers of styryl dyads of TEMPO-based alkoxyamines 7 ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the added SG1 pushing the equilibrium between dormant and active chains towards the dormant chains, resulting in slower polymerizations [32,33]. A similar effect of additional free SG1 nitroxide was observed for the polymerizations done at 110°C.…”
Section: Results and Discussion 31 Synthesis Of Ppa Homopolymersmentioning
confidence: 57%
“…In all the cases, polystyrene standards ranging from 580 to 225×10 4 g/mol were used for calibration. 1 The purified copolymer was then analyzed by 1 …”
Section: Characterizationmentioning
confidence: 99%